Optimalisasi Aliran Turbin Aksial yang Menghasilkan Daya dalam Sistem Siklus Rankine Organik Berdasarkan Studi Numerik - Haolia Rahman; Fitri Wijayanti Wijayanti; Gun Gun Ramdlan Gunadi; Albait Malikul Izzat (Infotekmesin, 2026)
Low-capacity Organic Rankine Cycle (ORC) turbines play an important role in utilizing low- to medium-temperature heat sources. This study aims to investigate the effects of working-fluid inlet temperature and turbine rotational speed on the power output and efficiency of an axial ORC turbine, as well as to determine the operating conditions that provide optimal performance. A Computational Fluid Dynamics (CFD)-based numerical simulation was conducted using SolidWorks Flow Simulation. The turbine analyzed in this study was a single-stage axial turbine equipped with eight half-round blades and operated with R134a as the working fluid. Simulations were performed at an inlet pressure of 2 MPa with inlet temperatures of 80°C, 90°C, and 100°C, and rotational speeds of 1500 rpm and 3000 rpm. The evaluated parameters included mass flow rate, enthalpy change, torque, input power, output power, and turbine efficiency. The simulation results showed that increasing the rotational speed from 1500 rpm to 3000 rpm improved the turbine power output. The highest output power of 14,064 W was achieved at 100°C and 3000 rpm, while the highest efficiency of 10.68% was obtained at 80°C and 3000 rpm. These findings indicate that rotational speed has a significant influence on turbine performance, whereas higher inlet temperatures do not necessarily result in the highest efficiency. The results of this study provide a useful basis for optimizing the design and operating conditions of axial ORC turbines for low-temperature heat recovery applications.